Glissonean approach for hepatic inflow control in minimally invasive anatomic liver resection: A systematic review. (23rd February 2021) - Morimoto, Mamoru; Tomassini, Federico; Berardi, Giammauro; Mori, Yasuhisa; Shirata, Chikara; Abu Hilal, Mohammed; Asbun, Horacio J.; Cherqui, Daniel; Gotohda, Naoto; Han, Ho‐Seong; Kato, Yutaro; Rotellar, Fernando; et al.
Abstract: Background: The Glissonean approach has been widely validated for both open and minimally invasive anatomic liver resection (MIALR). However, the possible advantages compared to the conventional hilar approach are still under debate. The aim of this systematic review was to evaluate the application of the Glissonean approach in MIALR. Methods: A systematic review of the literature was conducted on PubMed and Ichushi databases. Articles written in English or Japanese were included. From 2, 390 English manuscripts evaluated by title and abstract, 43 were included. Additionally, 23 out of 463 Japanese manuscripts were selected. Duplicates were removed, including the most recent manuscript. Results: The Glissonean approach is reported for both major and minor MIALR. The 1st, 2nd and 3rd order divisions of both right and left portal pedicles can be reached following defined anatomical landmarks. Compared to the conventional hilar approach, the Glissonean approach is associated with shorter operative time, lower blood loss, and better peri‐operative outcomes. Conclusions: Glissonean approach is safe and feasible for MIALR with several reported advantages compared to the conventional hilar approach. Clear knowledge of Laennec's capsule anatomy is necessary and serves as a guide for the dissection. However, the best surgical approach to be performed depends on surgeon experience and patients' characteristics. Standardization of the Glissonean approach for MIALR is important. Abstract : Highlight Morimoto and colleagues reviewed and summarized the literature focusing on hepatic inflow control in minimally invasive anatomic liver resection (MIALR), with the aim of evaluating the application and outcomes of the Glissonean approach in MIALR. Although different opinions remain, this manuscript provides current evidence on the Glissonean approach in MIALR.